How the COVID-19 Pandemic Impacted on Integrated Care Pathways for Lung Cancer: The Parallel Experience of a COVID-Spared and a COVID-Dedicated Center - Pasello, Giulia; Menis, Jessica; Pilotto, Sara; Frega, Stefano; Belluomini, Lorenzo; Pezzuto, Federica; Caliò, Anna; Sepulcri, Matteo; Cernusco, Nunzia Luna Valentina; Schiavon, Marco; Infante, Maurizio Valentino; Damin, Marco; et al. (Frontiers in Oncology, 2021)
Introduction The COVID-19 pandemic has proved to be a historic challenge for healthcare systems, particularly with regard to cancer patients. So far, very limited data have been presented on the impact on integrated care pathways (ICPs). Methods We reviewed the ICPs of lung cancer patients who accessed the Veneto Institute of Oncology (IOV)/University Hospital of Padua (Center 1) and the University Hospital of Verona (Center 2) before and after the COVID-19 pandemic, through sixteen indicators chosen by the members of a multidisciplinary team (MDT). Results Two window periods (March and April 2019 and 2020) were chosen for comparison. Endoscopic diagnostic procedures and major resections for early stage NSCLC patients increased at Center 1, where a priority pathway with dedicated personnel was established for cancer patients. A slight decrease was observed at Center 2 which became part of the COVID unit. Personnel shortage and different processing methods of tumor samples determined a slightly longer time for diagnostic pathway completion at both Centers. Personnel protection strategies led to a MDT reshape on a web basis and to a significant selection of cases to be discussed in both Centers. The optimization of patient access to healthcare units reduced first outpatient oncological visits, patient enrollment in clinical trials, and end-of-life cancer systemic treatments; finally, a higher proportion of hypofractionation was delivered as a radiotherapy approach for early stage and locally advanced NSCLC. Conclusions Based on the experience of the two Centers, we identified the key steps in ICP that were impacted by the COVID-19 pandemic so as to proactively put in place a robust service provision of thoracic oncology.